Features of foreign investment in business companies that occupy a dominant position in the commodity market - Milchakova, Olesya Vladimirovna (Юридические исследования, 2024)
The object of the study is certain issues of the procedure for foreign investments in strategic sectors of the economy. The subject of the study is devoted to the procedure for making foreign investments in business entities that occupy a dominant position in the commodity market. The dominant economic entity has market power, which provides an opportunity to shape the economic environment by determining the number of market participants, the behavior of suppliers of goods (works, services) and their consumers. The author examines the issues of necessary regulatory approvals of transactions of foreign investors for the acquisition of assets of dominant entities, as well as general antitrust and special rules for determining the existence of a dominant position in business entities operating in various sectors of the economy. The methodological basis of the study was based on systematic and formal legal methods, as well as the method of technical and legal analysis. The conclusions of the study are based on the constitutionally significant goals of ensuring national defense and state security, Russian legislation provides for the need to obtain additional regulatory approvals for foreign participation in business entities that occupy a dominant position on the market. At the same time, the book value of assets and the amount of revenue of a foreign investor does not matter, a group of persons to which he belongs, as well as a business entity whose assets are planned to be acquired by a foreign investor (a group of persons to which a foreign investor belongs), unlike transactions subject to approval within the framework of antimonopoly control. In some cases, the control of foreign investments applies special rules for determining the fact of market dominance for some business entities, which differ from the rules of antimonopoly legislation.